Haruskah Indonesia Peduli pada Prahipertensi di kalangan Dewasa Muda? - Ratri Ciptaningtyas (The Indonesian Heart Association, 2012)
Background. Prehypertension is a classification of blood pressure refere to people with systolic blood pressure (SBP) between 120 and 139 mmHg or diastolic blood pressure (DBP) 80 and 89 mmHg. Studies reported eighty-five percent of prehypertensions have one ormore CVD risk factor compared to normotensions. However, little was known about the epidemiology of prehypertension among young adult in Indonesia.Methods. Analyses were conducted based on 2007 National Health Survey (Riskesdas) with 55,347 people aged 18 to 25 in 33provinces in Indonesia. Results. All demographic parameters but sex showed significant differences between prehypertension and normotension participants. The result of themultivariable logistic regression analysis showed that the geographic area of residence, marital status, education level, occupation,overweight, smoking cessation and daily cigarette use, alcohol consumption, fruit and vegetable consumption, and mental health disorder were revealed to be significant risk factors of prehypertension among young Indonesian adults. Conclusion. These results further underline the need for routine BP measurements in young adults to identify subjects with prehypertension who should be the target of lifestyle modification.Future implications from study result point out the need to prioritize nutrition education which involve psychosocial management and healthy lifestyle promotion among young adult in Indonesia.